Students' Perception of Example-Based Learning in Software Modeling Education - Bonetti, Tiago Piperno; Dias, Matheus Molina; Silva, Williamson; Colanzi, Thelma Elita (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2023: Anais do XXXVII Simpósio Brasileiro de Engenharia de Software, 2023)
Teaching software modeling is challenging because it involves understanding and applying complex theoretical concepts to design structural models. In this sense, empowering students with the knowledge and skills necessary for the software industry is a challenge, intensified by the majority adoption of traditional (expositive) lectures, where students are passive subjects in the learning process. Adopting methodologies where the student plays an active role during learning is necessary to deal with this challenge. Example-Based Learning (EBL) is an active teaching methodology that satisfies such a condition. It uses worked examples to demonstrate how to perform a given task or acquire a given skill. In this context, this work aims to investigate, from the student’s perspective, how EBL can contribute (or not) to learning class diagram modeling. To do so, an exploratory study was carried out in which instructors used a support portal whose objective was to guide them in applying EBL in their classes. The study was conducted with 40 volunteer students from three different Informatics and Computer Science classes at a Brazilian university. The results showed that students had a positive perception of EBL, reporting that it facilitated the understanding of theoretical concepts, improved the connection between theory and practice, helped to deal with errors, and promoted essential skills for software development. These results corroborate that EBL is an efficient approach to the software modeling learning process, which can contribute to encouraging instructors to adopt this type of methodology in teaching Software Modeling.